Tecnologias Digitais da Informação e Comunicação e o processo de expansão e integração da educação superior no MERCOSUL - Sahb, Warlley Ferreira (2016)
The increase in higher education provision is a process supported or performed by the governments of several countries. This phenomenon is related to the increased level of economic processes demands as well as the democratization of countries regarding schooling of the population, increasing, therefore, social participation. Furthermore, it can also be related to the increasing demand for professional qualification. The expansion of higher education, while encouraging trans-national integration processes, also contributes to the fight against regional and social inequalities. This thesis analyzes the process of integration of Information and Communication Digital Technologies (ICDT) with the curriculum. Herein, we demonstrate that this is constituted as a formative element for the development and cultural and social unity of the MERCOSUR countries. It is important to consider the need and importance of guaranteeing the right to education and its strategic role for development in Latin America. Compared to the process of educational integration, which happened in Europe by the Bologna process, it is possible to observe a similar process in South America. By conducting a literature review, bibliographic and documentary research and by conducting a PhD research at the Open University of Portugal (UAb-PT), we could observe that the process of integration of ICDT in schools and curricula has taken place in an environment marked by strong social changes and expansion of technological resources, which are available to schools and universities. With this research, we aim at evaluating a critical contextualization of the concept of technology and its penetration in social relationships, causing several changes and implementing new concepts in schools, such as digital culture, culture of innovation and education in the age of mobility. Recognizing the evidence and importance of integrating ICDT in the school context, but at the same time, doing a critical and contextualized review, it appears that the inclusion of ICDT in education - in schools or universities - will not automatically bring changes or innovations to the curriculum. With regard to the importance of establishing a common transnational curricular base, there is the need for a proposal for the collaboration among Latin American countries, ranging from a basic platform of studies, plans, practices and training for Education. This basic platform can be named transnational curriculum. This is not exactly to propose a curriculum for schools within MERCOSUR or even in Latin America, but a curriculum from which it allows to plan and operate structuring training programs, dialogue, discussion and publication for educators, managers and students from the countries. We conclude that the expansion and educational integration requires a joint work among all parties involved in the process, to strategically and democratically deal with the diverse and complex issues of the coordination of ICDT in schools and curriculum